Simplify this expression: 13 + (–12) – (–5) = ?
A. 6
B. –30
C. 30
D. –6

Question

Asked 9/12/2012 9:04:03 AM

Updated 3/21/2014 9:16:01 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [3/21/2014 9:16:01 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|KnowledgeGirl|Points 185|

Question

Asked 9/12/2012 9:04:03 AM

Updated 3/21/2014 9:16:01 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [3/21/2014 9:16:01 AM]

Rating

8

13 + (–12) – (–5)

13 - 12 + 5

1 + 5

= 6

13 - 12 + 5

1 + 5

= 6

Added 3/21/2014 9:16:00 AM

This answer has been confirmed as correct and helpful.

Simplify the following expression: 35 + (–13) + (+8) – (–6).
A. 44
B. 24
C. 36
D. 50
**Weegy:** 35 + (–13) + (+8) – (–6) = 35 - 13 + 8 + 6 = 36 (More)

Question

Updated 7/7/2015 3:11:00 PM

0 Answers/Comments

Solve the following equation: 6y – 20 = 2y – 4.
A. y = 4
B. y = 16
C. y = 3
D. y = 2
**Weegy:** 6y – 20 = 2y – 4, 6y - 2y = -4 + 20, 4y = 16, y = 16/4, y = 4 (More)

Question

Updated 9/30/2016 5:57:31 AM

0 Answers/Comments

If five times a number plus two is 17, what is the number?
A. 5
B. 3
C. 2
D. 7
**Weegy:** If five times a number plus two is 17, the number is 3. 5n + 2 = 17,
5n = 17 - 2, 5n = 15, n = 15/5, n = 3 (More)

Question

Expert Answered

Updated 3/21/2014 9:14:15 AM

0 Answers/Comments

37,309,657

questions answered

There are no comments.